ANALISIS KEBIJAKAN PADA JURUSAN TEKNIK ELEKTRO DENGAN MENGGUNAKAN MATRIKS MACMILLAN DALAM RANGKA IMPLEMENTASI STRATEGI KOMPETITIF MENGHADAPI MASYARAKAT EKONOMI ASEAN - Doddy Maulana (Politeknik Negeri Malang, 2018)
The objective of this research is to obtain the best policy at Electro Engineering Department, State Polytechnic of Malang to face ASEAN Economic Society. The method of the Research is: MacMillan Matrix Analysis, and Determination of strategic policy. The results of the research are the improvement of policy at Electro Engineering Department to face ASEAN Economic Society which covering aspects: teaching and education, students and graduate, research and community service, education management systems, human resources, finance, quality assurance systems and facilities.